Glacier elevation changes in the western Nyainqentanglha Range of the Tibetan Plateau as observed by TerraSAR-X/TanDEM-X images. Issue 12 (2nd December 2017) - Zhang, Qibing; Zhang, Guoshuai
ABSTRACT: Global warming greatly affects glacier retreat, which in turn influences local water resources and sea level altitudes. We used Landsat Operational Land Imager (OLI) images to extract glacier outlines in the western Nyainqentanglha Range, then used TerraSAR-X/TanDEM-X images and SRTM-C DEM to calculate changes in glacier elevation using a differential interferometric synthetic aperture radar (DInSAR) approach. The decreasing rate of glacier elevation in the western Nyainqentanglha Range was −0.30 ± 0.07 m per year (m yr −1 ) from 2000 to 2014. The annual thinning rate of the northern slope (−0.46 ± 0.07 m yr −1 ) was faster than that of the southern slope (−0.24 ± 0.07 m yr −1 ). We investigated two exemplary glacier sites in details: Zhadang glacier on the northern slope and Gurenhekou glacier on the southern slope. The annual elevation change of 39 points on Zhadang glacier calculated by the DInSAR and Real Time Kinematic Global Position System (RTK-GPS) seperately have a correlation coefficient of 0.88. The mass balance change of Gurenhekou glacier is −0.21 ± 0.06 m water equivalent per year (m w.e. yr −1 ) from DInSAR, which is similar to the value of −0.31 m w.e. yr −1 determined via stakes and snow pits from 2005 to 2010.